Analysis of Reforming the Pension System of Ukraine: Implementation Problems and Development Prospects - Poznyakova, O.; Panchuk, N.; Burtseva, O. (Економічний вісник Донбасу, 2020)
Pension provision is an element of the pension system that ensures sustainable socio-economic development of the state as a whole. The article discusses the current problems of the pension system in Ukraine, ways to overcome and directions for its improvement. Determination of the further development and reform of the pension system aimed at ensuring the financial stability of the solidarity system. Introduction of the development of the pension system, taking into account the peculiarities of the current situation in the country, ways of reforming social insurance. The compulsory accumulative pension system is considered. Its introduction to retirees for two centuries. The advantages of the funded system, what it is based on, and its main contingent of citizens are analyzed. Principles of pension accrual, pension entitlements, old-age pensions, pension transfer, minimum and maximum pension in the course of reforms. Analyzed, introduced by introducing amendments to some legislative acts of Ukraine regarding the increase in pensions. The demographic state of the population is considered. The article proves that the main strategic directions for improving the pension reform is the introduction of changes in the demography of the population; percentage of ERUs, when calculated for each entrepreneur separately (respectively, from the group of an individual entrepreneur to the type of activity); open your deposit account for the savings system in the public domain; to enable pensioners to work (to improve their knowledge with practitioners, to provide an opportunity to work with modern equipment, programs) to determine the dates for the introduction of the second level and the age category of participants; to establish and improve the work of the organization of pension provision; to show confidence in the reforms of the Pension Fund bodies to the population.
Nowadays, constant monitoring of the achievement of the strategic goals of the reform of the pension system and pension provision and the adoption of fundamental decisions to overcome strategic gaps is quite an urgent issue and requires further research. У статті розглянуто сучасні проблеми пенсійної системи в Україні, шляхи подолання та напрями її вдосконалення. Розглянуто загальнообов’язкову накопичувальну систему пенсійного забезпечення. Проаналізовано переваги накопичувальної системи, принципи нарахування пенсії, права на пенсію, пенсії за віком, перерахування пенсії, мінімальний та максимальний розмір пенсії під час реформ. Проаналізовано зміни до деяких законодавчих актів України щодо підвищення пенсії. У статті обґрунтовано стратегічні напрями стосовно вдосконалення пенсійної реформи України. Наразі постійний моніторинг досягнення стратегічних цілей реформи пенсійної системи та пенсійного забезпечення та прийняття ґрунтовних рішень стосовно подолання стратегічних розривів доволі актуальне питання та потребує подальшого дослідження. В статье рассмотрены современные проблемы пенсионной системы в Украине, пути преодоления и направления ее совершенствования. Рассмотрена общеобязательная накопительная система пенсионного обеспечения. Проанализированы преимущества накопительной системы, принципы начисления пенсии, права на пенсию, пенсии по возрасту, перерасчет пенсии, минимальный и максимальный размер пенсии в ходе реформ. Проанализированы введенные изменения в некоторые законодательные акты Украины относительно повышения пенсии. Обоснованы основные стратегические направления по совершенствованию пенсионной реформы Украины. Постоянный мониторинг стратегических целей реформы пенсионной системы и пенсионного обеспечения и принятие фундаментальных решений по преодолению стратегических разрывов довольно актуальный вопрос и требует дальнейшего исследования.